Tourism Development and Energy Consumption Pattern in Langtang Valley of Nepal Himalayas - Chapagain, Prem Sagar (Journal of Development and Administrative Studies, 2016)
Langtang is one of the three major trekking destinations in Nepal. Tourism development in Langtang was started since after the establishment of Langtang National Park in 1976. Langtang is the nearest mountain trekking route from Kathmandu. About 12000 tourists visit annually in Langtang Valley. The Langtang valley from Syabrubesi to Kyanjing has rich physical, biological and cultural diversity which has been the center of tourism activities in Langtang region. This paper aims to trace out the tourism development trend and energy consumption pattern by hotels and lodges of the region. There are three major tourist destinations i.e. Lamahotel, Langtang, and Kyanjing in the Langtang valley where there are 49 hotels altogether. Initially, by 2000, hotels were concentrated at Lamahotel, then to Langtang village and finally to Kyanjing. Many tourist hubs in mountain including the Langtang valley use firewood as a major source of energy. The per bed/day firewood consumption is slightly varied in different altitude in the valley. The amount of firewood consumption decreases with increasing altitude and the distance from the source of firewood collection places. The annual firewood consumption is the highest in Lama hotel that is 457 kilogram/bed followed by Langtang with 460 kilogram and Kyanjing (400kg). It is important that the Bhattis consume more firewood. Hotels with less than 20 beds consume more firewood compared to big hotels suggests firewood energy threshold in the mountain tourism hub. LP gas and cow dung cake are other energy sources. The big hotels having more than 20 beds use more LG gas compared to smaller hotels.The Journal of Development and Administrative Studies (JODAS)Vol. 23(1-2), pp. 69-83